2014
DOI: 10.1371/journal.pone.0115729
|View full text |Cite
|
Sign up to set email alerts
|

Expression Patterns of HvCKX Genes Indicate Their Role in Growth and Reproductive Development of Barley

Abstract: Cytokinin oxidase/dehydrogenase proteins (CKX) are encoded by a multigene family of CKX genes with a varying number of members depending on species. For some of the genes, spectacular effects on grain production in selected cereals have been observed. Despite the fact that partial or full length sequences of most HvCKX genes in barley (Hordeum vulgare) have already been published, in most cases their specific biological functions have not been reported. Detailed expression patterns for five HvCKX genes in diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
65
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(77 citation statements)
references
References 37 publications
10
65
0
2
Order By: Relevance
“…Knock-out mutation or silencing by RNAi of OsCKX2 in rice significantly increased grain number (Ashikari et al, 2005). The same effect of elevated grain number, spike number and yield was reported for RNAi-silenced HvCKX1 in barley (Zalewski et al, 2010; Zalewski et al, 2012; Zalewski et al, 2014) and repeated for the same gene under field conditions (Holubova et al, 2018). Moreover, significantly increased grain number per spike was found as the effect of the TaCKX2.4 gene silenced by RNAi (Li et al, 2018).…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…Knock-out mutation or silencing by RNAi of OsCKX2 in rice significantly increased grain number (Ashikari et al, 2005). The same effect of elevated grain number, spike number and yield was reported for RNAi-silenced HvCKX1 in barley (Zalewski et al, 2010; Zalewski et al, 2012; Zalewski et al, 2014) and repeated for the same gene under field conditions (Holubova et al, 2018). Moreover, significantly increased grain number per spike was found as the effect of the TaCKX2.4 gene silenced by RNAi (Li et al, 2018).…”
Section: Introductionsupporting
confidence: 57%
“…Active CKs can be metabolized via oxidation by cytokinin oxidase/dehydrogenase (CKX) or by activity of glycosyltransferases. Many reports have demonstrated that the irreversible degradation step by CKX enzyme plays an important role in regulation of cytokinin level in some cereals: maize (Brugiè re N, 2003), rice (Ashikari et al, 2005), barley (Zalewski et al, 2010; Zalewski et al, 2014) and wheat (Song et al, 2012; Zhang et al, 2012; Ogonowska et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Among them 2 genes coding for cytokinin- O -glucosyltransferases (ZOG), i.e., Medtr6g014660 and Medtr3g111140.1 and a gene coding for a cytokinin oxidase, i.e., Medtr4g118430.1 are significantly downregulated in Mtnf-ya1-1 roots compared to WT (A17) roots, both before inoculation and one day after inoculation. In Rice the suppression of ZOGs leads to a decrease in fasciculated root production (Kudo et al, 2012) while contradicting reports about the positive and negative effect of cytokinin oxidase on root growth exist (Köllmer et al, 2014; Zalewski et al, 2014). …”
Section: Discussionmentioning
confidence: 94%
“…As decreasing CKX activity is a target for enhancing yield in both monocots and dicots [41,62,63] it is important to be aware that any increased cytokinin may impact source-sink relationships. Particularly critical in peas may be PsCKX2, which is expressed in the imbibing seed: if this gene family member were to be down-regulated, this may impact severely on the release of nutrients from the cotyledon.…”
Section: Discussionmentioning
confidence: 99%